Impact of right-turn channelization on pedestrian safety at signalized intersections. (March 2020) - Jiang, Chaozhe; Qiu, Rui; Fu, Ting; Fu, Liping; Xiong, Binglei; Lu, Zhengyang
Highlights: Channelized right turns have been widely implemented to reduce traffic delay. The impact channelized right turns on pedestrian safety has not been addressed. The performance of different right-turn designs on pedestrian safety is compared. Surrogate safety and behavioral measures from multiple facets of safety were used. Channelized right turns increase pedestrian risks from different safety dimensions. Abstract: Channelized right turns or slip lanes have been widely implemented as an effective countermeasure of reducing traffic delay and number of conflicts between vehicles at signalized intersections. However, only a few studies have investigated the impact of channelized right turns (in left-band driving countries) on pedestrian safety. Channelized right turns may increase the risks for pedestrians since they bring pedestrian-vehicle interactions in a fully non-signalized environment. Furthermore, the increased turning radius at channelized lanes can lead to higher vehicle speeds. This paper investigates the impact of channelized right turns on pedestrian safety based on surrogate safety and behavior measures. Video data were collected from twelve signalized intersections in the city of Zunyi, China, involving three main types of right-turn designs: 1) non-channelized right-only lanes, 2) non-channelized right-through lanes, and 3) channelized right-turn lanes. Different measures are used, including interaction and behavior measures based on a recent-proposed Distance-Velocity model, the PET measurement, speed measurements, and observations of failures in interactions (pedestrian retreats and evasive maneuvers from pedestrians or vehicles). Results indicate that the design of channelized right-turn lane increases pedestrian risks at signalized intersections from different dimensions of safety. The impact of the nighttime condition on pedestrian safety was also compared. Pedestrians are safer at nighttime at non-channelized locations, while the impact of nighttime conditions on pedestrian safety at channelized intersections was not ascertained. Consequently, cities should be cautious to install channelized intersections as a safety countermeasure. Treatments are needed to improve pedestrian safety if channelized right turns are implemented.